ДОКТРИНА ІНФОРМАЦІЙНОЇ БЕЗПЕКИ УКРАЇНИ: ЗАВДАННЯ, ПРИНЦИПИ РЕАЛІЗАЦІЇ - Коминар, Назар Михайлович (SUPREMANCE OF LAW, 2018)
The article deals with the tasks and principles of the implementation of the Doctrine of Information Security of Ukraine. It is specified that as a tool of state influence on processes in the field of information security should be more actively use the interaction of information security actors, which is an open system of two-tier design with a centralized-segmental division of power between its main elements - the subjects of information security, defined by the Doctrine of Information Security of Ukraine.
Keywords: information; information security; Doctrine of information security; subjects of providing information security